PCI Girder Analysis on Bridge Structure (Case Study: Main Bridge Simpang Susun Cikulur STA 37+425.65 Serang-Panimbang Toll Road Project) - Rizka Apriliani; Soelarso Soelarso; Baehaki Baehaki; Zulmahdi Darwis; Midia Rahma; M. Hasbi Zuher (Jurnal Fondasi, 2026)
This study discusses the analysis of PCI Girder on bridge structures. The purpose of this study is to determine the pretension force, loss of prestress, and deflection that occur in the PCI Girder in the case study of the Main Bridge Sumpang Susun Cikulur STA 37+452,650 Serang-Panimbang Toll Road Project. The bridge that was used as a review in this study was a bridge with a span of 20.6 m. The structural element analyzed is the PCI Girder with 2 tendons. The loading regulations used in the analysis refer to SNI 1725:2016, and the analysis of the bridge structure is based on SNI 2847:2019. The results of the analysis showed that the PCI Girder on the Main Bridge Simpang Susun Cikulur STA 37+452.65, Serang-Panimbang Toll Road Project, received an initial prestressed force of 5833.14 kN and decreased to 4901.50 kN in the final condition. The loss of prestressed force that occurred consisted of 8% for immediate loss and 11.72% for time-dependent loss. In addition, the deflection experienced by the girder was 29.91 mm upward under the transfer condition, 13.48 mm upward due to short-term loading, and 60.45 mm downward due to long-term loading.